Mama’s petopia / Mohammad Fareed Qaisar Mohd Farizal - Mohd Farizal, Mohammad Fareed Qaisar (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
Isniah Binti Usin and Benjamin Pinto founded Cinta Mama Pets in 2014, and since then, it has transformed from a side gig to a bustling neighborhood business called Mama's Petopia. This pet shop has made a name for itself in the market by being a customer-focused business and by taking its cues from the fascinating world of small animals and cats. Mama's Petopia focuses on a wide variety of pet necessities, with an emphasis on items ranging from accessories to dietary supplements. The company's local roots are apparent; it is run by indigenous people, whose redesigned logo perfectly captures the spirit of their firm. The logo incorporates images of the house and its animal occupants, maintaining a unique style while adhering to the general concept of the pet shop. Under the motto "For Pet Lovers, By Pet Lovers," Mama's Petopia is dedicated to supplying exceptional products and services, affordable prices, and high-quality care and attention to a wide range of animal-loving customers. The business emphasizes accuracy and skill in its services, guarantees unmatched hospitality, and provides consumer and environmentally sustainable products. Due to issues with the original logo's visibility, Mama's Petopia decided to remodel it and came up with a catchphrase to draw in and keep customers. The rebranding endeavor focuses on visually appealing and structurally refined brand aspects, integrating corporate paraphernalia with the store's thematic ambiance. Influenced by prominent industry players' triumphant positive and negative logo designs, Mama's Petopia has repositioned itself as a strong competitor in the worldwide pet supply and retail market. The story culminates with a description of Mama's Petopia's development into a leading organization in the pet product services and sales sector, distinguished by accuracy, style, and creativity, with the goal of becoming a global leader.